2019
DOI: 10.1016/j.ajhg.2019.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic TARS Mutations Are Associated with Brittle Hair Phenotype

Abstract: Brittle and ''tiger-tail'' hair is the diagnostic hallmark of trichothiodystrophy (TTD), a rare recessive disease associated with a wide spectrum of clinical features including ichthyosis, intellectual disability, decreased fertility, and short stature. As a result of premature abrogation of terminal differentiation, the hair is brittle and fragile and contains reduced cysteine content. Hypersensitivity to UV light is found in about half of individuals with TTD; all of these individuals harbor bi-allelic mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 45 publications
6
51
0
1
Order By: Relevance
“…We here extend this classification, and highlight a possible contribution of protein translation disturbances in the pathophysiology of TTD. Recently, mutations in aminoacyl-tRNA synthetases were identified to cause TTD (Kuo et al, 2019, Theil et al, 2019 implying that a disturbed translation process, as shown in this study, might be causal for the developmental delay and neurodegeneration observed in TTD. This assumption is based on the hypothesis that only disturbances in a common cellular signaling pathway that is affected by all genes in this genotypical heterogenous disease can explain the phenotype.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We here extend this classification, and highlight a possible contribution of protein translation disturbances in the pathophysiology of TTD. Recently, mutations in aminoacyl-tRNA synthetases were identified to cause TTD (Kuo et al, 2019, Theil et al, 2019 implying that a disturbed translation process, as shown in this study, might be causal for the developmental delay and neurodegeneration observed in TTD. This assumption is based on the hypothesis that only disturbances in a common cellular signaling pathway that is affected by all genes in this genotypical heterogenous disease can explain the phenotype.…”
Section: Discussionsupporting
confidence: 55%
“…TTD is mainly attributed to a transcription syndrome (Compe, Genes et al, 2019, Theil, Mandemaker et al, 2017. However, recently discovered mutations in aminoacyl-tRNA synthetases that result in TTD may shift this classification towards a "gene expression syndrome" referred to a disturbed protein translation at the ribosome (Kuo, Theil et al, 2019, Theil, Botta et al, 2019. TFIIH mutations can also cause the premature aging disease Cockayne syndrome (CS) that resembles TTD with symptoms of developmental delay, microcephaly and neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…More than 60 disorders are associated with mutations in ARS genes and, depending on their individual genotype, follow both dominant or recessive inheritance patterns. [4][5][6][7][8][9][10] Cytosolic phenylalanyl-tRNA synthetase (FARS1) ranks among the most complex of the ARSs with a hetero-tetrameric structure, consisting of two FARS alpha (FARSA) and two FARS beta (FARSB) subunits. 11 The hypothesis that both genes may be associated with a similar multisystemic human disease, including features of interstitial lung disease, liver disease, neurological manifestations, and growth restriction (MIM: 619013, 613 658), needs further support.…”
Section: Introductionmentioning
confidence: 99%
“…. A very recent report introduced two individuals carrying TARS variants with trichothiodystrophy 43 , while we found a spastic hemiplagia patient (CP_014_1) with biallelic TARS variants, who presented overlapping phenotype including developmental delay, but without manifestation in hair or skin (Supplementary figure 4).…”
mentioning
confidence: 69%